2012
DOI: 10.2174/138955712800626719
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biology of Fascaplysin, a Potent Marine-Derived CDK-4 Inhibitor

Abstract: Marine natural products offer an abundant source of pharmacologically active agents with great diversity and complexity, and the potential to produce valuable therapeutic entities. Indole alkaloids is one of the important class of marine-derived secondary metabolites, with wide occurrence amongst variety of marine sources such as sponges, tunicates, algae, worms and microorganisms and have been extensively studied for their biological activities. Among this chemical family, a sponge-derived bis-indole alkaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 0 publications
0
61
0
Order By: Relevance
“…The marine sponge-derived bis-indole alkaloid Fascaplysin is effective against malaria [1], against bacterial, fungal, and viral infections [1], as well as against malignancy [1][2][3]. The efficacy against malignancy is at least in part due to activation of autophagy and apoptosis of tumor cells [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marine sponge-derived bis-indole alkaloid Fascaplysin is effective against malaria [1], against bacterial, fungal, and viral infections [1], as well as against malignancy [1][2][3]. The efficacy against malignancy is at least in part due to activation of autophagy and apoptosis of tumor cells [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Fascaplysin further counteracts angiogenesis by triggering apoptosis of endothelial cells [4]. Cellular mechanisms involved include inhibition of p56 tyrosine kinase and of cyclin-dependent kinase-4 [1,4], DNA intercalation [1] as well as activation of caspases [2].…”
Section: Introductionmentioning
confidence: 99%
“…It was later found to exert anti-proliferative activity against HeLa (ovarian cancer) cell line though apoptosis. Fascaplysin showed in vitro anti-angiogenic activity via vascular endothelial growth factor (VEGF) blockage, cell cycle arrest and apoptosis on human umbilical vein endothelial cells (HUVEC) [40]. It also showed selective inhibition of Cyclin-dependent kinase 4 (CDK4) and correspondingly arrested the cell cycle in the growth of multiple cancer cell types at the G0/1 phase.…”
Section: Fascaplysinmentioning
confidence: 99%
“…and recent studies showed that fascaplysin is an inhibitor of Cdk4, with an IC 50 about 0.55 µM, and induce apoptosis in a variety of cancer cells [91]. Since decrease in the Cdk4 activity, fascaplysin has also been revealed to be capable of inhibiting angiogenesis [92].…”
Section: Compounds That Disturbs the Growth Receptor Signaling Pathwaymentioning
confidence: 99%